EFFICIENCY OF THE SPECIFIC PREVENTION OF PNEUMOCOCCAL INFECTION IN CHILDREN ATTENDING PRESCHOOL INSTITUTIONS - Елкина, Татьяна Николаевна; Пирожкова, Наталья Игоревна; Грибанова, Ольга Александровна; Грибанова, Анастасия Сергеевна (Mother and Baby in Kuzbass, 2021)
The aim of the research – evaluation of the effectiveness of vaccination against pneumococcal infection in children attending preschool institutions. Materials and methods. A retrospective comparative study of outpatient cards of Novosibirsk preschoolers was carried out. The main group included children who received a full course of immunization with pneumococcal conjugate 13-valent vaccine, the control group included their unvaccinated peers. The nature of the course of acute respiratory infections in the first year of visiting a day care was analyzed. The processing of the material was carried out using a package of modern statistical programs. Results. Vaccinated children were less likely to suffer from acute respiratory infections during their first year of socialization. Diseases were more often mild, bacterial complications and the use of antibacterial drugs were recorded with a lesser frequency. In the group of unvaccinated preschoolers, on the contrary, acute respiratory pathology was recorded more often, mainly of moderate severity. Bacterial complications and the need for systemic antibiotic therapy were more often noted. Conclusion. It has been reliably proven that specific prevention of pneumococcal infection in children attending preschool educational institutions can reduce the frequency and severity of acute respiratory diseases together with reducing the risk of developing complications from the infection and preventing the antibiotics use.